Sonoelectrochemical investigation of silver analysis at a highly boron-doped diamond electrode. - Saterlay, A; Marken, F; Foord, J; Compton, R (Elsevier, 2000)
A study into the sonoelectroanalysis of silver at a highly boron-doped diamond electrode is presented, exploring the benefits of the introduction of power ultrasound and new electrode materials into classical electrochemical techniques. Both cathodic and anodic stripping voltammetry have been investigated in terms of their analytical suitability towards silver detection. Cathodic stripping voltammetry, via electrodeposited silver oxide, was affected by the unusual chemistry of the highly oxidising Ag(2+) species and the characterisation of this system is discussed in detail. Anodic stripping, via deposition of metallic silver on the bare boron-doped diamond electrode surface under ultrasound, coupled with square-wave voltammetry, was successfully employed in the development of a sensitive technique for the analysis of trace silver ions. A detection limit for Ag(+) of 10(-9) M for a 300-s deposition, with a linear range of at least two orders of magnitude, and the beneficial effects of controlling the speciation of Ag(+) via complexation with chloride ions are reported.